1979
DOI: 10.1055/s-0028-1097251
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids from Leaves and Flowers of Colchicum autumnale L.1

Abstract: The alkaloid content in fresh and dry leaves and flowers of Colchicum autumnale ,L. was studied. Results show that 2-and 3-demethylated derivatives of colchicine do not occur in extracts from fresh material but they are present in considerable quantity in material slowly dried before extraction due to enzymatic liberation. Demethylated products are not bound in form of glycosides, but are attached in an unknown manner to cell constituents. In addition to known alkaloi,ds we have found cornigerine, 2and 3-demet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Alkaloid extraction was carried out for all methanol extracts. The evaporation was done at 35°C, and during the study, direct light protection was provided (Malichova et al, 1979).…”
Section: Extraction Isolation and Determination Of Alkaloidsmentioning
confidence: 99%
“…Alkaloid extraction was carried out for all methanol extracts. The evaporation was done at 35°C, and during the study, direct light protection was provided (Malichova et al, 1979).…”
Section: Extraction Isolation and Determination Of Alkaloidsmentioning
confidence: 99%
“…In our earlier paper [11], we reported that the fresh material (leaves and flowers) did not contain 2-demethylcoichicine (II) which was found in variable quantities only in the dry material. It was assumed that the O-demethylated derivatives of colchicine (I), N-deacetyl-N-formylcoichicine (XI), and demecolcine (XVII) are intermediary degradation products or that these compounds are enzymatically liberated during drying from the bond with high molecular substances [11]. In dry material (stored over a long period), BucH-Great differences exist in the "coichicine" content (tropolone alkaloids of coichicine type) reported in the literature .…”
Section: Introductionmentioning
confidence: 86%
“…N1EK found a gradual decrease in the content of tropolone alkaloids [4]. 2-Demethylcolchicine (II) was not found in dry seeds, fresh corms, leaves and flowers [11,15], whereas 3-demethylcoichicine (III) was present in dry seeds and corms; the latter alkaloid might arise in seeds on hydrolysis of colchicoside [16,17]. All the fresh parts of the plant C. autumnale and C. byzantinum contain 2-demethyldemecolcine (XIX) and traces of 3-demethyldemecolcine (Alkaloid CC-7) (XX) [18].…”
Section: Antav'etalmentioning
confidence: 99%
See 2 more Smart Citations